Manajemen Sarana dan Prasarana dalam Menunjang Prestasi Belajar Siswa di MTs Assalam Penuguan Banyuasin - Anisa Fadillah; Rytha Petrossky; Sri Utami; Syafwatul Putria H (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
The existence of management of facilities and infrastructure to serve the entire community in the school through a joint effort to achieve goals both effectively and efficiently. The formulation of the research problem is; How to Manage School Facilities and Infrastructure to Support Student Learning Achievement at MTS Assalam. The aim of the research is to find out how the management of school facilities and infrastructure supports the achievement of student participants at MTS Assalam Penuguan Banyuasin. Qualitative research method, using a descriptive approach. Information is obtained from interviews, hand notes, documents and visual materials such as photos and videos, materials from the internet and other documents. As a result of the research, findings were obtained regarding: The availability of facilities and infrastructure in schools can make it easier for students and teachers in the learning process, if they have adequate facilities and infrastructure, teachers' strategies and skills in teaching and use the facilities and infrastructure appropriately. Complete educational facilities and infrastructure can create better learning conditions. Based on the research results, conclusions from interviews with management informants of facilities and infrastructure at MTS Assalam can be said to support student learning achievement, because at MTS Assalam the infrastructure is good. And the suggestion is that schools need to increase creativity and innovation in maintaining facilities and infrastructure. So doesn't cost too much money or procurement funds for maintenance. For example, holding a class wall cleaning competition. So that student creativity increases, maintenance is maintained and expenses for purchasing wall paint are minimized.